Nanoscale Curvature Regulates YAP/TAZ Nuclear Localization Through Nuclear Deformation and Rupture - Emmet A. Francis; Einollah Sarikhani; Vrund Patel; Dhivya Pushpa Meganathan; Leah Sadr; Anum Tahir; Zeinab Jahed; Padmini Rangamani (Advanced Science)
Abstract Nuclear translocation of the transcription regulatory proteins yes‐associated protein (YAP) and transcriptional coactivator with PDZ‐binding motif (TAZ) is a critical readout of cellular mechanotransduction. Recent experiments have demonstrated that cells on substrates with well‐defined nanotopographies demonstrate mechanoadaptation through a multitude of effects ‐ increased integrin endocytosis as a function of nanopillar curvature, increased local actin assembly on nanopillars but decreased global cytoskeletal stiffness, and enhanced nuclear deformation. How do cells respond to local nanotopographical cues and integrate their responses across multiple length scales? This question is addressed using a biophysical model that incorporates plasma membrane (PM) curvature‐dependent endocytosis, PM curvature‐sensitive actin assembly, and stretch‐induced opening of nuclear pore complexes (NPCs) in the nuclear envelope (NE). This model recapitulates lower levels of global cytoskeletal assembly on nanopillar substrates, which can be partially compensated for by local actin assembly and NE indentation, leading to enhanced YAP/TAZ transport through stretched NPCs. Using cell shapes informed by electron micrographs and fluorescence images, the model predicts lamin A and F‐actin localization around nanopillars, in agreement with experimental measurements. Finally, simulations predict nuclear accumulation of YAP/TAZ following rupture of the NE and this is validated by experiments. Overall, this study indicates that nanotopography tunes mechanoadaptation through both positive and negative feedback on mechanotransduction.